PENINGKATAN KETRAMPILAN MENULIS MELALUI PENERAPAN MODEL PEMBELAJARAN GROUP INVESTIGATION UNTUK SISWA KELAS X SMA NEGERI 2 ABUNG SEMULI TAHUN 2016 - Mariman Mariman (Edukasi Lingua Sastra, 2018)
The main aim of this research is to make the teaching learning of Bahasa Indonesia at class X of SMA Negeri 2 Abung Semuli, academic year 2016-2017 become interesting and effective. The research is classroom action research conducted in two cycles that involves plan, action, observation and reflection. The subject of the research was class X that consists of 32 students (18 females and 14 males ). There were three instruments used in the reseach : students’ writing ability , students’ activity, and learning achievement. This study found that the use of Group investigation model of learning can increase the effectiveness the Bahasa Indonesia learning process at class X. The effectiveness of learning process is shown by improvement of the achievement at (1) the percentage of students’ writing ability that reached the target from 68.95% (cycle 1) becomes 72,28 % (cycle 2) or increased 3,33 %.(2) The percentage of students’ activity in cycle 1 was 73,64 % became 76,42 % that meant the increased 2,78 %,(3) the persentage of learning achievement also increased from 75,97 % (cycle 1) to 78,22 % (cycle 2) , the increase was 2,25 %. The result of learning using Group investigation model is achieved through the following stages: (1) pre-activity, teacher prepared students by informing the learning objective, giving motivation, preparing the material and putting the students into groups. (2) main step, the students in group were distributed the topic problem, group presentation, personal task, plenary discussion, conclusion and (3) post-activity, making a resume of the material and teaching learning reflection.